CEREBRAL VENOUS AIR EMBOLISM IN A PATIENT WITH SUPERIOR VENA CAVA OCCLUSION - RADHIANA HASSAN; INTAN BAZILAH ABU BAKAR (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Introduction: Large cerebral venous air embolism (CVAE) is a rare but serious complication generally attributed to invasive central venous instrumentation or neurosurgical procedures. However, in patients with significant hemodynamic alterations, such as superior vena cava (SVC) occlusion, CVAE can develop through unique retrograde mechanisms following routine care. Case Report: A 58-year-old male with Stage 4 non-small cell lung carcinoma presented with new-onset headache. Thoracic computed tomography (CT) demonstrated neoplastic occlusion of the SVC by mediastinal lymphadenopathy. Subsequent brain CT revealed multiple air pockets within the superior sagittal sinus and left cavernous sinus. The patient was managed conservatively, with complete resolution of symptoms and air emboli on follow-up imaging 10 days later. Discussion: In the setting of SVC occlusion, elevated central venous pressure can reverse the physiological pressure gradient. Consequently, air introduced during routine upper extremity peripheral cannulation may migrate cephalad through the valveless internal jugular veins into the cerebral venous system, rather than flowing antegrade to the right heart. Conclusion: Clinicians must be aware of these abnormal hemodynamics and should consider using lower extremity intravenous access in this population to mitigate the risk of retrograde embolization.